The impact of the COVID-19 pandemic on students’ future online education behaviour - Luiela Magdalena Csorba; Dan-Cristian Dabija (Heliyon, 2024)
Background: The COVID-19-related pandemic has affected education hugely, particularly in terms of the massive shift towards online teaching and learning. Higher education students and professors have faced new challenges, which might improve future online education behaviour, based on online education experience and learning, and pedagogical strategies during the COVID-19 pandemic. Objective/Aim: The aim of this paper is to explore the views of Romanian students towards a possible future online education, highlighting their perceptions regarding the efficacy of digital online learning/pedagogical strategies and of the technological infrastructure, using as support theory the Input-Environment-Outcomes (I-E-O) model. Methods/Instruments: An empirical quantitative-based investigation was implemented; data being collected from almost 800 students in business and economics. Based on the proposed conceptual model, data were analysed with structural equations modelling via SmartPLS 3.0. Results: The novelty of the paper is that it tries to address students’ perceptions regarding the future of online education, by using a few constructs, some of them validated in the literature, in order to establish pertinent links between these and the future of digital education. Results reveal that Romanian students prefer face-to-face teaching rather than online courses. Conclusions/implications: In crisis situations, digital education might be the proper solution for future education, as it ensures effective education through efficient teaching-learning strategies and an advanced technological infrastructure.